Pengaruh Rasio Keuangan terhadap Prediksi Financial Distress dengan Model Grover, Ohlson, dan Zavgren pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2024 - Tiara, Zahratu; Devy, Tartila (ARZUSIN, 2026)
Financial distress is an important concern in financial studies because it can be used as an early indicator of a company’s potential bankruptcy. However, studies that specifically compare the effects of financial ratios on financial distress prediction using the Grover, Ohlson, and Zavgren models in pharmaceutical companies in Indonesia remain limited. This study aims to analyze the effects of Return on Assets (ROA), Current Ratio (CR), Debt to Asset Ratio (DAR), and Total Asset Turnover (TATO) on financial distress prediction in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study used a quantitative approach with a causal design. The research sample consisted of 10 pharmaceutical companies selected through purposive sampling. Data were obtained from companies’ annual financial statements through the documentation method and analyzed using multiple linear regression with the assistance of EViews 13. The results showed that ROA and TATO had significant effects on financial distress prediction in the Grover, Ohlson, and Zavgren models. CR had a significant effect in the Grover and Zavgren models but was not significant in the Ohlson model, whereas DAR had a significant effect only in the Grover model. Simultaneously, ROA, CR, DAR, and TATO had significant effects on financial distress prediction in all three models. In addition, the Grover and Zavgren models demonstrated higher predictive ability than the Ohlson model. These findings contribute to the development of Agency Theory and Signaling Theory in explaining the relationship between financial ratios and financial distress. The practical implications of this study can serve as a basis for consideration by investors, creditors, company management, and regulators in identifying financial distress risk at an earlier stage.